TOPIC Nº 13.2 “PROPIEDADES DEL MCD Y EL MCM” MCD (kA; kB; kC) = k. MCD (A; B; C) MCM (kA; kB; kC) = k. MCM (A; B; C) MCD ( Ak ; Bk ; Ck ) = MCD ( A ; B ; C) k MCM ( Ak ; Bk ; Ck ) = MCM ( A ; B ; C) k MCM (A; B) x MCD (A; B) = A x B 1. Si A = 18B y...
More
TOPIC Nº 13.2 “PROPIEDADES DEL MCD Y EL MCM” MCD (kA; kB; kC) = k. MCD (A; B; C) MCM (kA; kB; kC) = k. MCM (A; B; C) MCD ( Ak ; Bk ; Ck ) = MCD ( A ; B ; C) k MCM ( Ak ; Bk ; Ck ) = MCM ( A ; B ; C) k MCM (A; B) x MCD (A; B) = A x B 1. Si A = 18B y MCD(A;2B) = 32, calcular A + B MCD(A; 2B) = 32 MCD(18B; 2B) = 32 2B. MCD(9; 1) = 32 2B. 1 = 32 2B = 32 32 B= 2 ⇒ B = 16 A = 18B A = 18(16) A = 288 ⇒ A + B = 288 + 16 = 304
Less